Characteristics of Allan-Herndon-Dudley Syndrome in Chinese children: Identification of two novel pathogenic variants of the SLC16A2 gene - Zhang, Qiang; Yang, Qi; Zhou, Xunzhao; Qin, Zailong; Yi, Shang; Luo, Jingsi (Frontiers in Pediatrics, 2022)
Objective The aim of this study was to identify causative variants associated with Allan-Herndon-Dudley syndrome (AHDS) in two unrelated Chinese families, and to determine their potential pathogenicity. We also summarized the core clinical symptoms of AHDS by reviewing the related literature. Methods Genomic DNA was isolated from the peripheral blood of AHDS patients and their family members. Whole exome sequencing (WES) was performed on the proband from each family to identify the candidate variants. Subsequently, Sanger sequencing was used to verify the identified candidate variants and to assess co-segregation among the available family members. In silico prediction combined with 3D protein modeling was conducted to predict the functional effects of the variants on the encoded protein. Results Two novel hemizygous variants of SLC16A2, c.1111_1112insGTCTTGT (Gly375fs*6) and c.942delA (Val315fs*28), were detected in two patients. We compared the clinical symptoms of the patients with all patients with AHDS reported in China and those reported in the literature. While both our patients presented symptoms mostly consistent with AHDS, Patient 1 had no abnormal brain structure and thyroid function, and yet showed other symptoms including lactic aciduria, conjunctival hyperemia, vomiting, laryngeal stridor, low immunoglobulin and iron levels. Conclusions This study expands the mutation spectrum of AHDS and has clinical value for variant-based prenatal and postnatal screening for this condition. Doctors often have difficulty identifying AHDS by using clinical symptoms. WES can help to identify specific disorder when diagnosis cannot be made based on symptoms alone.